Floristic inventory of the montane forest patches adjacent to Lake Pomacochas, Bongará province, Amazonas Department - Rascón, Jesús (2020)
Tropical montane forests have great diversity, as they are made up of trees with an irregular distribution. They are usually accompanied by shrubs, herbaceous plants, epiphytes, and climbers, which is why montane ecosystems have significant heterogeneity. In the present investigation, we studied the vegetation of the montane forest patches adjacent to Lake Pomacochas, a tropical high Andean lake affected by seasonal events of moderate to heavy rains and droughts, in the department of Amazonas, in northern Peru. An inventory was carried out in which 103 vascular plant species belonging to 56 families were recorded, collected in the montane forest patches adjacent to Pomacochas Lake, along 49 provisional sampling stations. The native species Cinchona officinalis L. and Baccharis latifolia (Ruiz & Pav.) Pers. stood out for their cultural importance and is the most affected by socioeconomic activities such as cattle ranching.